Pengaruh Beasiswa KIP Kuliah Terhadap Motivasi Belajar Mahasiswa pada Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Maumere: Penelitian - Nurul Tsaltsa Aprinda; Rusli Hereng; Nur Chotimah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Learning motivation in this study plays an important role in an individual's academic success. The KIP-Kuliah scholarship can influence learning motivation and help evaluate the effectiveness of the program, as well as encourage students to achieve higher academic performance. This study aims to determine the influence of the KIP-Kuliah scholarship on the learning motivation of students in the Faculty of Teacher Training and Education at the University of Muhammadiyah Maumere. The research method used is quantitative, with data collected through questionnaires. The sample consisted of 65 students who received the KIP-Kuliah scholarship from the 2021–2022 academic year. Data analysis techniques included prerequisite tests and statistical analysis tests. The results showed that the KIP-Kuliah scholarship had a positive and significant influence on students' learning motivation. The t-test results showed a t-count value of 7.083, which is greater than the t-table value of 1.669, and a significance value of 0.000 < 0.05, indicating that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted.